Development of a Wide Bandwidth Massive Eight Dissimilar Radiating Element Multiband MIMO Antenna for mm-Wave Application - Sarade, S.; Ruikar, S. D. (Engineering, Technology & Applied Science Research, 2022)
This paper proposes a massive MIMO antenna operating on 6GHz frequency as millimeter-wave. It consists of eight dissimilar-shaped radiating elements. The radiating element of the antenna is designed using square shape with different cut slots. Parasitic elements and defected ground structure are introduced for the enhancement of the correlation coefficients and total active reflection coefficients of the MIMO antenna. The rectangular shape parasitic elements are placed between the square radiating patches. The ground plane consists of rectangular shape defected ground structures. The antenna is constructed on the FR-4 substrate. Parameters such as isolation, cross-correlation, and bandwidth are enhanced. The obtained through simulations antenna parameters values of return loss, isolation, cross-correlation, total active reflection coefficients, and bandwidth are less than -10dB, less than -9.30dB, less than 0.16, less than 0.00015, and greater than 200MHz respectively. The antenna operates on various bands with fractional bandwidth greater than 3% for a frequency of 6GHz. This antenna is useful for a variety of applications in wireless systems.